The concept of a smart contract: advantages and current situation of legal regulation in the Republic of Kazakhstan - Boranbay, S.S.; Juchnevicius, E. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In the article the current provisions of the legal regulation of smart contracts were outlined, the relevance of which will grow as such contracts spread in various spheres and areas of life. Thus, the main problem of regulating relations on the use of a smart contract is the ambiguity of its legal essence, the lack of regulation in legislation, including in the Civil Code of the Republic of Kazakhstan. At the same time, some advantages of a smart contract are clearly shown by examples, which will help facilitate the process of concluding, changing, terminating and executing contracts. The main advantages of a smart contract are also discussed in detail, such as automation, transparency, security, efficiency, low intermediary costs, decentralization, flexibility and programmability. In the research, the authors touched upon the problems of fulfilling obligations in debt relations, the potential advantages and assistance of a smart contract in enforcement proceedings. The result of the exploration is a formulated definition of a smart contract and the identification of specific potential advantages of this type of non-traditional contracts. The authors summarize the results, noting the absence of a legal definition of a smart contract in the legislation of the Republic of Kazakhstan, the exclusively declarative nature of its legal regulation; the ambiguity of the range of public relations where contracts in this form are applicable, which does not allow the widespread dissemination and use of a smart contract.
Смарт келісім-шарт тұжырымдамасы: артықшылықтары және Қазақстан Республикасында құқықтық реттелуінің қазіргі жағдайы
Концепция смарт-контракта: преимущества и нынешнее положение правового регулирования в Республике Казахстан
Keywords: blockchain; smart contracts; digitalization; innovative technologies; automation; information technology; e-commerce; Ethereum; Solidity; cryptography